Perth and Fremantle past and present - Nevill, Simon ([Fremantle], Western Australia : Simon Nevill Publications, 2007)
A beautifully presented record of the lives of West Australians. A photographic journey through time, incorporating a brief history behind many of the photographs. Also includes a short history of the Nyoongar people and early settlement.
Includes bibliographical references and index.
Keywords: Perth (W.A.) -- History -- Pictorial works; Fremantle (W.A.) -- History -- Pictorial works; Perth, (W.A.) -- History; Fremantle, (W.A.) -- History; Western Australia -- Fremantle; Western Australia -- Perth; Australian; History